2014
DOI: 10.1021/es502641f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Avian Aryl Hydrocarbon Receptor and Inter-species Sensitivity Variations by Polychlorinated Diphenylsulfides

Abstract: It was hypothesized that polychlorinated diphenyl sulfides (PCDPSs) can potentially interact with an aryl hydrocarbon receptor (AHR) and thereby cause adverse effects in wildlife like birds. A recently developed avian AHR1-luciferase report gene (LRG) assay was used to assess the interaction between avian AHR1 and 18 PCDPSs and to compare the interspecies sensitivity among chicken, ring-necked pheasant, and Japanese quail by PCDPSs. Most of the tested PCDPSs could activate the AHR1-mediated pathways in avian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Thus, the revised qAOP using EC Threshold could also be used as a tool to more rapidly assess the potential for cross‐species differences in sensitivity to lower‐potency DLCs. In addition, there are currently only a few studies that have investigated the sensitivity to other agonists of the AhR across species; therefore, the extent of cross‐species differences in sensitivity to these chemicals warrants further investigation (Zhang et al 2014, 2016; Head et al 2015; Franci et al 2018; Bak et al 2019). The revised qAOP using EC Threshold could enable the chemical applicability domain of the qAOP to be better defined regarding inclusion of other agonists of the AhR, which are often lower‐potency agonists, such as PAHs, OH‐/MeO‐PBDEs, or PCDPSs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the revised qAOP using EC Threshold could also be used as a tool to more rapidly assess the potential for cross‐species differences in sensitivity to lower‐potency DLCs. In addition, there are currently only a few studies that have investigated the sensitivity to other agonists of the AhR across species; therefore, the extent of cross‐species differences in sensitivity to these chemicals warrants further investigation (Zhang et al 2014, 2016; Head et al 2015; Franci et al 2018; Bak et al 2019). The revised qAOP using EC Threshold could enable the chemical applicability domain of the qAOP to be better defined regarding inclusion of other agonists of the AhR, which are often lower‐potency agonists, such as PAHs, OH‐/MeO‐PBDEs, or PCDPSs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, maximal response is often not reached in this in vitro AhR transactivation assay for PCBs, including all mono‐ ortho PCBs, which can be more than 3 orders of magnitude less potent than the prototypical reference compound, 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin (2,3,7,8‐TCDD), but can still represent a risk to wildlife (Van den Berg et al 1998; Manning et al 2012). Further, certain polycyclic aromatic hydrocarbons (PAHs) and some contaminants of emerging concern, such as hydroxylated and methoxylated polybrominated diphenyl ethers (OH‐/MeO‐PBDEs) and polychlorinated diphenylsulfides (PCDPSs), can be agonists of the AhR but typically do not elicit maximal response in this in vitro AhR transactivation assay (Zhang et al 2014, 2016, 2018; Bak et al 2019). Because these low‐potency agonists do not reach maximal response in this in vitro AhR transactivation assay, the current qAOP cannot be reliably used to predict dose–response curves of early life stage mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among birds, chicken is the most sensitive to DLCs . For TCDD, the sensitivity of Japanese quail is 100‐fold less than that of chicken . Although a complete understanding of the reasons underling differences in sensitivities among species is not yet available , a factor is differential binding of DLCs to the ligand binding domain of the AhR caused by differences among sequences of amino acids of the ligand binding domain, especially at positions 324 and 380 of the AhR1–ligand binding domain of birds .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, Zhang et al examined the aromatic hydrocarbon receptor (AhR) effect of 18 types of PCDPSs, and the results demonstrated that the relative potency (relative to 2,3,7,8-TCDD) values of 2,4,4′,5-tetra-CDPS, 2,2′,3′,4,5-penta-CDPS and 2,2′,3,3′,4,5,6-hepta-CDPS are 1.0 × 10 −4 , 1.1 × 10 −4 and 6.8 × 10 −4 , respectively. 9 The relative potency values of the three PCDPSs are higher than those of several dioxin-like PCBs (DL-PCBs), such as PCB-118 and PCB-189, whose TEF values proposed by the World Health Organization (WHO) in 2005 are all 3.0 × 10 −5 . 10 These studies provided evidence that PCDPSs had certain ecological and health risks.…”
Section: ■ Introductionmentioning
confidence: 99%